People’s Participation in Community Development: Ban Khon Khwang Community, Mueang District, Prachinburi Province, Thailand - Joomsoda, Lalida; Tirasuwanvasee, Sirikarn (Community and Social Development Journal, 2022)
People’s participation is necessary in development in organization, community, and national level. In Thailand, there is Local administration, which is decentralized from the government, is one of the sectors that people can participate directly. It has autonomy to serve the needs of people in the local society. Therefore, people’s participation is important to make their rights and evaluate the local administration. The objective of this study is to the impact of between perceptions of information on community development and factors that supporting participation that effect people’s participation in the community.This study was conducted in Prachinburi is one of the prosperous provinces in Thailand by using quantitative method and there were 112 respondents. The results showed that perception of information on community development including information about policy, planning, and operations, and factors supporting participation including training attendance, activity attendance, and group membership had effect on people’s participation for 72.70 percent. The recommendation was that the government sector or related organizations could enhance the level of people’s participation by increasing the channels that provide information to the community and encourage people attending the training, activities and group membership.